An extended inner-outer factorisation algorithm based on the structure of a transfer function matrix inverse - Zhang, Wei; Zhao, Chunhui; He, Xing; Zhang, Weidong (International journal of systems science, 2016)
In this paper, the structure feature of the inverse of a multi-input/multi-output square transfer function matrix is explored. Instead of complicated advanced mathematical tools, we only use basic results of complex analysis in the analysing procedure. By employing the Laurent expression, an elegant structure form of the expansion is obtained for the transfer function matrix inverse. This expansion form is the key of deriving an analytical solution to the inner-outer factorisation for both stable plants and unstable plants. Different from other computation algorithm, the obtained inner-outer factorisation is given in an analytical form. The solution is exact and without approximation. Numerical examples are provided to verify the correctness of the obtained results.